Patterns of variability in Azorella selago Hook. (Apiaceae) on sub-Antarctic Marion Island : climate change implications - Nyakatya, Mawethu Justice (Stellenbosch : Stellenbosch University, 2006)
Thesis (MSc)--University of Stellenbosch, 2006. ENGLISH ABSTRACT: Understanding the responses of species to climate change is a scientific problem that requires urgent attention, especially under current conditions of global climate change. The large and rapid rates of climate change reported for sub-Antarctic Marion Island makes the island highly suitable for studying the biotic consequences of climate change. Furthermore, the extreme environments on the island result in a close coupling of the biotic (e.g. population dynamics) and abiotic (e.g. climate) factors. Therefore, examining the response of the dominant and keystone plant species on the island, Azorella selago Hook. (Apiaceae), to climate-associated environmental change (e.g. temperature) may provide insight into how A. selago and the associated species communities will be affected by climate change. This study described the variability in microclimate temperatures associated with A. selago across altitudinal gradient and between the eastern and western sides of Marion Island. Microclimate temperatures were also compared to the island’s Meteorological data to determine variation between temperatures experienced by A. selago cushion-plants in the field and those recorded at the island’s Meteorological Station. Temperature variation inside and outside A. selago cushions was also examined. Azorella selago cushions were found to have a buffering effect on temperature, such that species occurring epiphytically on A. selago experience more moderate temperatures than the surrounding environment. However, A. selago were found to experience more extreme temperatures than temperatures recorded at the Meteorological Station. Therefore, A. selago may possibly experience greater environmental warming than recorded by the Meteorological Station. While temperatures decline with altitude, temperature conditions on the western side of the island were more temperate than the eastern side. This presents the first record of temperature conditions on the western side of ...